"It feels incongruent to talk about reducing shame when I have to spell ’s-e-g-g-s’ on TikTok": Navigating Platform Moderation as Sex Education Creators on Social Media - Pinch, Annika Caroline; Suenzo, Facundo; Cruz, Ignacio; Liang, Calvin; Ross Arguedas, Amy (AoIR Selected Papers of Internet Research, 2026)
Sex education in the U.S. remains a contested issue, with no federal mandate and varying state policies, often restricting content related to LGBTQ+ and marginalized communities. People increasingly turn to social media platforms like TikTok for sexual education. However, platform moderation—shaped in part by laws like FOSTA-SESTA—imposes severe restrictions on sex education content, limiting its accessibility and undermining creators’ work. This study examines how sex education professionals navigate platform moderation on TikTok and Instagram. Through in-depth interviews with 15 sex education creators, we explore the challenges posed by content restrictions, particularly the use of “algospeak” to circumvent moderation. While strategies to bypass moderation, such as misspelling words, avoiding certain terms altogether, or using code words, can help creators circumvent moderation, they introduce new tensions such as further reinforcing stigma around sex and undermining their professional credibility. Creators report increased labor in justifying their content choices and frustration with platform priorities, which inconsistently moderate educational material while allowing harassment and hate speech to persist. Our findings highlight how ruptures in platform governance are experienced by creators and actively produce new fractures, reinforcing and reshaping the dynamics of knowledge and power online.